On optimal control of the Wiener process - Kolemaev, V. (Lithuanian Mathematical Journal, 1963)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:В. А. Колемаев. К оптимальному регулированию винеровского процессаV. Kolemaev. Optimalaus Vinerio proceso reguliavimo klausimu